PREEKLAMSIA BERAT - Soufni Morawati; Helwi Nofira (Nusantara Hasana Journal, 2025)
Severe preeclampsia is a hypertensive disorder of pregnancy characterized by elevated blood pressure and signs of end-organ damage occurring after 20 weeks of gestation. This condition remains a major cause of maternal and perinatal morbidity and mortality worldwide. Severe preeclampsia may present with systolic blood pressure ≥160 mmHg or diastolic blood pressure ≥110 mmHg, accompanied by proteinuria or other manifestations such as thrombocytopenia, impaired liver function, renal insufficiency, pulmonary edema, and neurological disturbances. The pathophysiology involves abnormal placentation, endothelial dysfunction, and systemic inflammatory responses. Management of severe preeclampsia requires prompt diagnosis, close maternal and fetal monitoring, blood pressure control, seizure prophylaxis with magnesium sulfate, and timely delivery as definitive treatment. Early recognition and appropriate management are essential to reduce complications and improve maternal and neonatal outcomes.